Congenital blindness limits allocentric to egocentric switching ability - Ruggiero, Gennaro; Ruotolo, Francesco; Iachini, Tina (Experimental brain research, 2018)
Many everyday spatial activities require the cooperation or switching between egocentric (subject-to-object) and allocentric (object-to-object) spatial representations. The literature on blind people has reported that the lack of vision (congenital blindness) may limit the capacity to represent allocentric spatial information. However, research has mainly focused on the selective involvement of egocentric or allocentric representations, not the switching between them. Here we investigated the effect of visual deprivation on the ability to switch between spatial frames of reference. To this aim, congenitally blind (long-term visual deprivation), blindfolded sighted (temporary visual deprivation) and sighted (full visual availability) participants were compared on the Ego–Allo switching task. This task assessed the capacity to verbally judge the relative distances between memorized stimuli in switching (from egocentric-to-allocentric: Ego–Allo; from allocentric-to-egocentric: Allo–Ego) and non-switching (only-egocentric: Ego–Ego; only-allocentric: Allo–Allo) conditions. Results showed a difficulty in congenitally blind participants when switching from allocentric to egocentric representations, not when the first anchor point was egocentric. In line with previous results, a deficit in processing allocentric representations in non-switching conditions also emerged. These findings suggest that the allocentric deficit in congenital blindness may determine a difficulty in simultaneously maintaining and combining different spatial representations. This deficit alters the capacity to switch between reference frames specifically when the first anchor point is external and not body-centered.